Zhong Hui (Chung Hui, 225–264 C.E.) in Internet Encyclopedia of Philosophy - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2007)
Zhong Hui (Chung Hui) was a major philosophical figure during China’s early medieval period (220-589 CE). An accomplished interpreter of the Laozi and the Yijing, Zhong Hui contributed significantly to the early development of xuanxue—literally “learning” (xue) of the “dark” or “mysterious” (xuan) Dao (“Way”), but sometimes translated as “Neo-Daoism“. He also was a major political figure whose ambition eventually led to his untimely demise. Virtually all of Zhong Hui’s writings have been lost, which perhaps explains why he has been given scant attention by students of Chinese philosophy. Had he not failed in his attempt to overthrow the regime of his day, no doubt his writings would have been preserved and given the attention they justly deserve. In particular, his views on human “capacity and nature” (caixing), as developed in his interpretation of the Laozi, are major contributions to xuanxue philosophy, which dominated the Chinese intellectual scene from the third to the sixth century CE. In contrast to other thinkers of the time, who argued that capacity and nature are the same (tong), different (yi), or diverge from one another (li), Zhong Hui argued that they coincide (he). In effect, he proposed that what is endowed is potential, which must be carefully nurtured and brought to completion through learning and effort. While one’s native endowment is not sufficient, one must have some material to begin with in order to achieve the desired result. Thus, it cannot be said that the latter has nothing to do with the former.